Prevalence of paternal perinatal depressive mood and its relationship with maternal depression symptomatology: An Italian study - Cattaneo, Maria Caterina; Macchi, Elena Alessandra; Salerno, Roberta; Chiorino, Valentina; Roveraro, Sara; Barretta, Francesco; Fontana, Camilla Barbara; Mosca, Fabio (International Journal of Advanced Nursing Studies, 2015)
Background: Literature shows that the birth of a child is a vulnerability moment for the mental well-being of both parents.Objectives: estimate the prevalence of a depressive symptomatology in an Italian sample of new fathers during the first six months postpartum and provide its association with maternal mood.Methods: 244 neo- parents filled the Italian version of the Edinburgh Postnatal Depression Scale (EPDS) and a General Information Questionnaire between 2/5 days after delivery during the hospitalization in the Mother-infant Department of an Italian hospital and after 2 and 6 months postpartum by mailed.Results: in the first week postpartum, 6.65% of fathers had a EPDS score â‰¥ 10, this percentage decreases to 2.63% at 2 months and 2.59% at 6 months postpartum. Previous history of anxiety/panic attacks in fathers was a risk factor for a depressive symptomatology of them after 2 and 6 months postpartum. Paternal and maternal depressive mood were correlated most of the times and associated especially after births when a depressed father is more than 5 time frequently associated to a depressed mother 2 months later.Conclusions: experimental data suggest that neo-fathers experiment depressive symptoms especially in the immediate postpartum when their mood is associated with maternal mood in a significant way. Health care professionals should pay great attention to the neo-parental couple mood.